High-resolution patterning of silver conductive lines by adhesion contrast planography. (6th August 2015) - Kusaka, Yasuyuki; Koutake, Masayoshi; Ushijima, Hirobumi
Abstract: We developed printed electronics compatible planographic printing methods that enable single-micrometer-order patterning with high rectangularity and thickness uniformity. Instead of conventional planographic printing methods where selective wetting is used for pattern generation, an adhesive latent image produced on a silicone surface is exploited for patterning in the proposed printing methodologies. We further investigated the fundamental mechanisms of the proposed methods by focusing on adhesion contrasts between the blanket, printing area, and non-printing area of a printing plate (PP) and determined that printing is feasible when a simple magnitude relation of adhesions is satisfied for thin layers of size ranging from approximately 50 nm to 100 nm. Latent image formation can be carried out via a simple ultraviolet exposure of the silicone surface, thereby enabling the rapid prototyping of printed device fabrications. The easily preparable, single material-based flat PPs developed in this study have the advantages of flexibility in pattern designs, washing process, fabrication cost, and pattern-rewriting capability compared with the conventional printing methods in which raised surfaces such as stamps or clichés are required for patterning.